Expression of proinflammatory cytokines and proinsulin by bone marrow-derived cells for fracture healing in long-term diabetic mice - Hitomi Fujikawa; Hideto Kojima; Tomoya Terashima; Miwako Katagi; Takafumi Yayama; Kosuke Kumagai; Kanji Mori; Hideki Saito; Shinji Imai (BMC Musculoskeletal Disorders, 2023)
Abstract Background Diabetes mellitus (DM) causes bone dysfunction due to poor bone quality, leading to severe deterioration in patient of quality of life. The mechanisms of bone metabolism in DM remain unclear, although chemical and/or mechanical factors are known to disrupt the homeostasis of osteoblasts and osteoclasts. The purpose of this study was to identify the changes of osteoblasts and osteoclasts under long-term hyperglycaemic conditions, using a mouse fracture model of long-term hyperglycemia (LT-HG). Methods C57BL/6J mice and green fluorescent protein (GFP) -positive bone marrow transplanted C57BL/6J mice with LT-HG, maintained under a state of hyperglycaemia for 2 months, were used in this study. After the experimental fracture, we examined the immunohistochemical expression of proinsulin and tumor necrosis factor (TNF) -α at the fracture site. C57BL/6J fracture model mice without hyperglycaemia were used as controls. Results In the LT-HG mice, chondrocyte resorption was delayed, and osteoblasts showed an irregular arrangement at the callus site. The osteoclasts were scattered with a decrement in the number of nuclei. The expression of proinsulin was confirmed in bone marrow derived cells (BMDCs) with neovascularization 2 and 3 weeks after fracture. Immunopositivity for TNF-α was also confirmed in immature chondrocytes and BMDCs with neovascularization at 2 weeks, and the number of positive cells was not decreased at 3 weeks. Examination of GFP-grafted hyperglycaemic mice showed that the majority of cells at the fracture site were GFP-positive. Immunohistochemistry showed that the rate of double positives was 15% for GFP and proinsulin and 47% for GFP and TNF-α. Conclusion LT-HG induces an increase in the number of proinsulin and TNF-α positive cells derived from BMDCs. We suggest that proinsulin and TNF-α positive cells are involved in both bone formation and bone resorption after fracture under hyperglycaemic conditions, resulting in the delay of bone healing.